Above and beyond meat: the role of consumers' dietary behavior for the purchase of plant-based food substitutes - Cristopher Siegfried Kopplin; Theresa Maria Rausch (Review of Managerial Science, 2021)
Shrinking meat intake levels and simultaneously increasing consumption of plant-based products among consumers suggest that consumers' dietary behavior implies the purchase of plant-based food substitutes. We contribute to the literature by investigating the most important determinants of consumers' dietary behavior and attitude towards plant-based food substitutes and whether consumers' dietary behavior is of relevance for the attitude towards plant-based food substitutes. Data of 1,363 consumers was used for structural equation modeling as well as necessary condition analysis. Consumers' dietary behavior is found to play only a minor role in attitude formation towards plant-based food substitutes. Dietary behavior is primarily influenced by animal welfare concerns. We did not find environmental concerns, consumers' perceived effectiveness, and health consciousness to influence dietary behavior. However, as consumers associate a high standard of animal welfare with healthiness and food safety, following a plant-based diet due to animal welfare concerns might be an altruistic pretext for health consciousness as an egoistic motive.
Keywords: M10; M30; O30; Q01; 650; Dietary behavior; Structural equation modeling; Necessary condition analysis; Plant-based food substitutes; Health; Environmental concerns; Animal welfare